(untitled) (Research, Society and Development, 2020)
Corn and sorghum are the main energy sources used in the diets of ruminants in our country. These two cereals have two characteristics that can hinder the absorption and use of starch by animals. They have two striking characteristics that hinder the absorption and use of starch by animals. The first is related to the consistency of the endosperm, classified as floury or hard, preventing the maximum use of the material, and the second is the protein matrix that covers the starch granules, functioning as an excellent physical-chemical barrier in the protection against weather conditions, problems harvesting and attacking insects and / or rodents. Processing over grains can be used as a way to improve the factors that limit their absorption, breaking the protein matrix that covers the starch granules, favoring the performance of digestive enzymes. The objective is to bring arguments and evidence on the efficiency of corn processing in the form of rehydration and silage, on aspects of ruminal degradability, improvement in feed conversion and increase in production. To this end, a review was carried out through scientific articles, analyzing the corn processing techniques and their performance in the productive characteristics of ruminants. Being able to conclude that the processing on the grain, can increase the nutritional value of corn with vitreous endosperm, improving the zootechnical aspects in the nutrition of ruminants.